Validation of 2 commercial Neospora caninum antibody enzyme linked immunosorbent assays - Wu, John T.Y. (2002)
This is a validation study of 2 commercially available enzyme linked immunosorbent assays (ELISA) for the detection of antibodies against Neospora caninum in bovine serum. The results of the reference sera (n = 30) and field sera from an infected beef herd (n = 150) were tested by both ELISAs and the results were compared statistically. When the immunoblotting results of the reference bovine sera were compared to the ELISA results, the same identity score (96.67%) and kappa values (K) (0.93) were obtained for both ELISAs. The sensitivity and specificity values for the IDEXX test were 100% and 93.33% respectively. For the Biovet test 93.33% and 100% were obtained. The corresponding positive (PV+) and negative predictive (PV−) values for the 2 assays were 93.75% and 100% (IDEXX), and 100% and 93.75% (Biovet). In the 2nd study, competitive inhibition ELISA (c-ELISA) results on bovine sera from an infected herd were compared to the 2 sets of ELISA results. The identity scores of the 2 ELISAs were 98% (IDEXX) and 97.33% (Biovet). The K values calculated were 0.96 (IDEXX) and 0.95 (Biovet). For the IDEXX test the sensitivity and specificity were 97.56% and 98.53%, whereas for the Biovet assay 95.12% and 100% were recorded, respectively. The corresponding PV+ and PV− values were 98.77% and 97.1% (IDEXX), and 100% and 94.44% (Biovet). Our validation results showed that the 2 ELISAs worked equally well and there was no statistically significant difference between the performance of the 2 tests. Both tests showed high reproducibility, repeatability and substantial agreement with results from 2 other laboratories. A quality assurance based on the requirement of the ISO/IEC 17025 standards has been adopted throughout this project for test validation procedures.